2013
DOI: 10.1016/s1470-2045(13)70309-7
|View full text |Cite
|
Sign up to set email alerts
|

Purged versus non-purged peripheral blood stem-cell transplantation for high-risk neuroblastoma (COG A3973): a randomised phase 3 trial

Abstract: Summary Background Myeloablative chemoradiotherapy and immunomagnetically purged autologous bone marrow transplantation has been shown to improve outcome for patients with high-risk neuroblastoma. Currently, peripheral blood stem cells (PBSC) are infused after myeloablative therapy, but the effect of purging is unknown. We did a randomised study of tumour-selective PBSC purging in stem-cell transplantation for patients with high-risk neuroblastoma. Methods Between March 16, 2001, and Feb 24, 2006, children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
294
2
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 268 publications
(308 citation statements)
references
References 26 publications
5
294
2
7
Order By: Relevance
“…All patients received HR-NB induction regimens. 5,6,30,31 Therapy before relapse included isotretinoin in 85 (84%) patients and anti-G D2 mAb in 51 (50%) patients. Sites of relapse were osteomedullary (BM and/or bone) (nD34), osteomedullary plus soft tissue (n D 31), or soft tissue (n D 36).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…All patients received HR-NB induction regimens. 5,6,30,31 Therapy before relapse included isotretinoin in 85 (84%) patients and anti-G D2 mAb in 51 (50%) patients. Sites of relapse were osteomedullary (BM and/or bone) (nD34), osteomedullary plus soft tissue (n D 31), or soft tissue (n D 36).…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…1 Before the routine use of immunotherapy, 3-5 year progression-free survival (PFS) rates in national studies were 20-40%, [2][3][4][5][6] even with inclusion of patients with what is now known to be intermediate-risk NB. 7 The randomized study of the Children's Oncology Group showed significantly better outcome in patients treated post-ASCT with the anti-G D2 chimeric mAb ch14.18 plus granulocyte-macrophage colony-stimulating factor (GM-CSF) plus interleukin-2.…”
Section: Introductionmentioning
confidence: 99%
“…The reason to this was considered to be either incomplete purging or residual tumour in the patient. These findings suggest that non-purged peripheral blood stem cell transplants are acceptable to support myeloablative therapy in highrisk neuroblastoma patients [30,31]. Tumour cell purging also significantly increases the price of the procedure, which further questions its necessity.…”
Section: Discussionmentioning
confidence: 99%
“…62 Subsequent studies simplified the intensity of the conditioning; dropping the TBI and using two or three drugs. 63,64 As the importance of the high-dose block of therapy has evolved from a 'kill or cure' approach to a cytoreductive cassette in overall therapy, the TRM has fallen from over 10% in an earlier era to the current 2%. 63 Figure 1.…”
Section: Building On a Platform Of High-dose Melphalanmentioning
confidence: 99%
“…63,64 As the importance of the high-dose block of therapy has evolved from a 'kill or cure' approach to a cytoreductive cassette in overall therapy, the TRM has fallen from over 10% in an earlier era to the current 2%. 63 Figure 1. 100-day TRM and year of high-dose procedure for neuroblastoma (with permission, from Ladenstein et al 60 ).…”
Section: Building On a Platform Of High-dose Melphalanmentioning
confidence: 99%